Installation Parameters, Pile Performance and Importance of Testing - Maurice Bottiau (Deep Foundations Institute, 2014)
"Abstract When addressing the performance of deep foundations, many parameters play a role, from adequate soil investigation to performance monitoring and testing. The correct understanding of pile construction, though, remains crucial. After a long period of empirical design and regulations, the last decades have been the ones of theoretical considerations and extensive codes writing. The interaction between technology and design, however, still plays a determinant role. The introduction of hydraulics and the exponential increase in available power on one hand, the miniaturization and the introduction of electronics in control and monitoring systems on the other hand have exerted a major influence on new foundation systems or the evolution and control of existing systems. It appears important to try to take execution related parameters and their control during execution more deeply into account when assessing the final result of the deep foundations and the achieved level of safety and reliability. In this contribution, we will try to analyze how systems, equipment and pile production monitoring and testing can influence the pile performance, and if/how this influence could/should be translated in adapted safety or installation factors. This analysis will run through different categories of piles: driven, augercast and displacement auger piles and bored piles. INTRODUCTIONThe global performance of a deep foundation depends on different aspects (Poulos, 2003):1. Ground investigation2. Design and analysis3. Construction4. Testing5. Performance monitoring6. Remediation and performance enhancementThis paper intends to address the importance of pile construction and the control of it on the final performance of the pile-group of piles. There has been an increasing interest for theoretical analysis over the last 20 years, followed by an increasing impact of regulation and codes. Without denying the importance of the latter, the author wants to point out how installation procedure and project specific parameters can largely influence the reliability of the deep foundation. In this context, detailed and prescriptive standards can miss their objective of intended improvement of accuracy and reliability, but even worse they can adversely impact engineering judgment. In today’s construction world, it is possible to gather installation information which can be of outmost importance for the final deep foundations performance. Therefore, the increase or decrease of installation reliability through adequate pile testing and performance monitoring should be emphasized and should be taken into account in the codes. This is the case already in most advanced codes, but in a limited and insufficiently refined way. After reviewing how codes deal with this issue today, we will show some recent examples of unexpected results due to pile installation. We will try to put these examples into a broader perspective by highlighting some reference and/or recent literature considerations. Finally we will try to summarize how pile testing and installation documentation can increase reliability and attempt to open the debate on how codes could/should allow for more engineering judgment."